Short- and long-term outcomes of laparoscopic versus open gastrectomy after neoadjuvant chemotherapy: A case-control study using a propensity score matching method - Qinchuan Yang; Changming Zhang; Haikun Zhou; Weidong Wang; Bo Shan; Chao Yue; Ruiqi Gao; Zhiyu Guo; Yannian Wang; Gang Ji; Xiaohua Li (Surgery Open Science, 2023)
Background: Neoadjuvant chemotherapy (NACT) is increasingly becoming the recommended treatment for locally advanced gastric cancer (LAGC) with promising results. According to previous reports, few studies have evaluated the benefits of laparoscopic gastrectomy (LG) after NACT. Methods: 135 patients from our center who underwent gastrectomy with NACT were available, including 41 patients of LG and 94 OG between July 2018 and July 2022. To reduce selection bias, we used the nearest neighbor method and set caliper = 0.2 for 3:1 matching between LG and OG groups for propensity score matching method (PSM). After PSM, the matched 41 patients with LG and 80 patients with OG formed the cohort, respectively. Univariate and multivariate Cox analyses were performed on all variables to determine independent risk factors associated with survival. Results: LG had a longer operating time compared to OG [260.00 min (220.00 min, 300.00 min) vs. 200.00 min (160.00 min, 260 min), P < 0.001]. The estimated blood loss, metastatic lymph nodes (LN), total LN examined, postoperative hospital stays, blood transfusion (P>0.05) and the incidence of postoperative complications did not show statistical differences from the OG group (P = 0.084). The type of surgery (LG vs. OG) did not show a significant risk propensity in the univariate and multivariate Cox analysis (HR = 0.69, P = 0.36, 95 % CI: 0.31–1.53). Through the Kaplan-Meier curves, a certain trend showed that the LG group had a better long-term survival outcomes than the OG group, although there was no statistical difference between two groups (P>0.05). Conclusion: LG is a promising treatment option for LAGC patients receiving NACT and had an acceptable safety and efficacy compared to OG.